Advances in textile engineering : selected, peer reviewed papers from the 2011 International Conference on Textile Engineering and Materials, (ICTEM 2011), 23-25 September, 2011, Tianjin, China - Wang, Rui; Liu, Huawu (Advanced materials research ;, 2011)
This book, with its internationally peer-reviewed papers, covers the subject areas of Textile Science and Technology, Textile Dyeing and Finishing, Textile Machinery and Equipment, Apparel Design and Merchandising and New Trends in the Textile Industry. It will be of interest to anyone working in these subject areas. Review from Book News Inc.: This work presents peer-reviewed papers from a September 2011 conference held in Tianjin, China. The papers are organized in sections on textile science and technology, textile dyeing and finishing, textile machinery and equipment, apparel design and me.